Redefining And Reassignment Of Trust Worthiness For Devices In Mobile Grid - Grantej Vinod Otari, Dr. V. R. Ghorpade , Dr. S. H. Dhanani (International Journal of Advanced Science and Technology, 2020)
Mobile Technology And Grid Technology Can Be Combined Together To Provide A Distributed Collaborative Environment In The Form Of Mobile Grid Network, Where The Resources Can Be Shared Securely, Transparently And Cooperatively To Perform The Task Or A Job Efficiently And Reliably. The Resources In Such Mobile Grid Network Are Highly Dynamic, Heterogeneous And Open In Nature. This Makes The Network Vulnerable To Active And Passive Attacks Made By Selfish And Malicious Nodes In The Network. Detecting Such Malicious Nodes And Preventing Them To Selfishly Participate In The Network Is The One Of The Most Critical Security Service. This Security Service Can Be Implemented By Developing A Comprehensive Trust Management System. The Proposed Trust Management System In This Paper Is Based On Fuzzy Lattice Concept. The Proposed Model Classifies The Mobile Nodes Based On Their Trust Value As Highly Trusted, Average And Less Trusted. The Node With The Trust Value Below The Threshold Is Considered As Malicious Node And Prevented From Participating In The Network. Evaluating The Results Of Analysis Show That The Proposed Trust Model Using Fuzzy Lattice Method Provides Comparatively More Efficient Results In Terms Of Trust Computation Time And Resources Utilized To Compute The Trust Such As Battery, Cpu Etc.